Wireless Mote Based Explosive Detection Land Rover using EC Sensor (WEDLRE) - Vaddi Manasa; K.Raghava Rao (Institute of Advanced Engineering and Science, 2015)
As continues attacks in the world from terrorists countries warning us to be aware of those attacks like Explosive attacks, hijacks etc., which will cause huge damage to the life and property in all over the world. Among these explosive attacks is most effective to life and wealth of a country. To overcome such attacks and to save the life an intense research has done to know the characterization of the explosives, Detection Methods are also improvised. To save our next generation and escape from threats a new detection methodology has been implemented to detect the explosives at all places and the proposed system is called “Wireless Explosive detection Land Rover using ECS”. In this system chemical sensors, Quartz sensors etc., are used on the motes. By using the RF Camera a continuous surveillance can be done throughout the places like malls, rooms, houses, streets, etc., if any explosive is detected then without any delay the explosive location and timeout to explode and area that effect if explode details will be sent to the Police control room to diffuse the explode device with in time. A message will also be sent to the nearby hospitals to rescue the people.